SAT0301 Vasospastic Severity and Digital Ischemia during Cooling is Related to Nail-Fold Capillaroscopic Pattern in Patients with Secondary Raynaud Phenomenon and Systemic Sclerosis. (10th June 2014) - Van Roon, A.M.; Smit, A.J.; van Roon, A.M.; Bootsma, H.; Mulder, D.J.
Abstract : Background: Microangiopathy, assessed as specific nail-fold capillaroscopic patterns (NCP), is a key feature and currently diagnostic criterion in the development of systemic sclerosis (SSc). In advanced SSc, NCP severity correlates clearly with fingertip perfusion at room temperature, potentially indicating structural narrowing of digital arteries. Whether this association is restricted to advanced SSc or may already be present in primary and secondary Raynaud's phenomenon (PRP and SRP) and early SSc has not been thoroughly investigated. Objectives: We hypothesize that the degree of vasospasm during cooling - as an index for digital ischemia - is associated with NCP severity in patients with PRP, SRP, and SSc. Methods: In 383 consecutive patients with suspected Raynaud's phenomenon without a history of digital ulcers (age 40, 5±17, 1, female 68%), NCP (assessed by widefield videocapillaroscopy), cooling and recovery fingertip photo-electric plethysmography (PPG), and clinical characteristics were retrospectively analyzed. NCP was performed at room temperature (24°C), and was classified as follows: "normal" (≤3 dilated capillaries per nail-fold, no giant capillaries), "mild" early (>3 dilated capillaries per nail-fold), "moderate" early (≥1 giant capillaries in total), "late" (≥1 giant capillaries in total and disrupted vascular configuration). One hand was cooled in water from 33°C to 6°C in steps of 3°C, each step lasting four minutes, followed by a recovery period of ten minutes in room air. Normal perfusion was defined as ≥4 fingers with normal PPG. PRP (N=112) was defined as normal NCP and negative ANA. Remaining patients were labeled SRP (N=212) consisting of 53 classifiable SSc patients (N=42 early (LeRoy criteria), N=11 limited cutaneous SSc). Mean ischemia time was defined as the mean time between loss of perfusion during cooling and reoccurrence at recovery of five fingers. Results: NCP was normal in 172, mild in 106, moderate in 65, and late in 40 patients. Vasospastic severity was positively associated with NCP severity (see figure). Mean ischemia time was positively associated with NCP severity (15, 9±9, 5, 18, 0±8, 8, 20, 7±9, 4, and 22, 4±10, 1 for normal, mild, moderate, late; p<0, 001 for trend), even when analyzing SRP (p=0, 003) or SSc (p=0, 025) alone. The prevalence of internal organ involvement increased with NCP severity (1%, 20%, 23% and 38%; p=0, 03). During cooling, the index finger and thumb lost perfusion significantly earlier than the other fingers (20, 8±5, 0 vs 18, 6±4, 8; p<0.001), irrespective of NCP severity. Conclusions: NCP severity is associated with the degree of digital ischemia during cooling, already in patients with early disease without a history of digital ulcers. This may implicate a role of digital artery vasospasms and recurrent ischemia in the development of nail-fold microangiopathy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4352